Seigniorage of fiat money and the maqasid al-shari'ah: the compatibility of the gold dinar with the maqasid - Mydin Meera, Ahamed Kameel; Larbani, Moussa (Jabatan Kemajuan Islam Malaysia, 2009)
Part I of the paper argued that fiat money is counterproductive to the attainment of the maqasid al-Shari’ah. In the present interest-based fiat monetary system one of the maqasid, namely, the protection of wealth (mal) cannot be realized, which in turn causes the other maqasid to be affected too. In this Part II paper we argue for commodity monies, like the gold dinar and silver dirham, as being compatible with the maqasid. Basically the paper concludes that the Islamic economic system is fundamentally a ‘barter’ system, i.e. an exchange economy where goods and services are exchanged value for value; but avoids the problems associated with barter by taking some of the commodities exchanged in the economy, that have the characteristics of money, as money; and gold is here argued as the best Shari’ah money